2013
DOI: 10.1016/j.yebeh.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy, cognition, and neuropsychiatry (Epilepsy, Brain, and Mind, part 2)

Abstract: Epilepsy is, of course, not one disease but rather a huge number of disorders that can present with seizures. In common, they all reflect brain dysfunction. Moreover, they can affect the mind and, of course, behavior. While animals too may suffer from epilepsy, as far as we know, the electrical discharges are less likely to affect the mind and behavior, which is not surprising. While the epileptic seizures themselves are episodic, the mental and behavioral changes continue, in many cases, interictally. The epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 184 publications
(210 reference statements)
2
34
0
1
Order By: Relevance
“…Considering these constraints, our EEG localization and fMRI results still exhibited a relatively good fit despite the low spatial resolution of EEG (Fuchs et al, 2002) and the low temporal resolution of fMRI. The widespread topography of scalp-recorded EEG theta effects with temporal and frontal peaks is similar to topographies in prior studies reporting MTL sources of theta power effects (Staudigl and Hanslmayr, 2013; Backus et al, 2016) and also fits with the assumption that deep sources are reflected in more widespread sensor-level effects (Dalal et al, 2013). Our source localization results are also corroborated by studies showing MTL theta effects similarly in sensor-level source reconstructions and intracranial recordings directly in the MTL (Dalal et al, 2013; Crespo-García et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Considering these constraints, our EEG localization and fMRI results still exhibited a relatively good fit despite the low spatial resolution of EEG (Fuchs et al, 2002) and the low temporal resolution of fMRI. The widespread topography of scalp-recorded EEG theta effects with temporal and frontal peaks is similar to topographies in prior studies reporting MTL sources of theta power effects (Staudigl and Hanslmayr, 2013; Backus et al, 2016) and also fits with the assumption that deep sources are reflected in more widespread sensor-level effects (Dalal et al, 2013). Our source localization results are also corroborated by studies showing MTL theta effects similarly in sensor-level source reconstructions and intracranial recordings directly in the MTL (Dalal et al, 2013; Crespo-García et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, simultaneous MEG and intracranial data from drug resistant epileptic patients strong ly suggest that MEG can detect hippocampal theta activity. With such recordings, it has been observed that surface magnetic activity and hip pocampal theta recorded with depth electrodes were practically over lapped, without phase delay (Dalal et al, 2013). Another simultaneous MEG iEEG study demonstrated that epileptic spikes generated in the hippocampus are sometimes observable with MEG (Santiuste et al, 2008).…”
Section: Successful Reconstruction Of Slow Theta Sources In the Hippomentioning
confidence: 99%
“…Much research has since been devoted to demonstrating this association in different populations. The notion of psychiatric and behavioral disorders as part of the spectrum of the expression of epilepsy has become generally accepted …”
Section: The Bidirectional Hypothesismentioning
confidence: 99%